Tok Bali Tiger Prawn Sdn. Bhd. / Ahmad Nashad Zakaria ... [et al.] - Zakaria, Ahmad Nashad; Awang, Sanusi; Mohd @ Alias, Aizam Juliana; Wan Zawawi, Wan Yusnida; Mohd Zin, Hasliza; Rasdin, Ros Noriza (Faculty of Sports Science and Recreation, 2000)
Type of business that we want to plunge is business partner that is to say livestock (Penaeus Monodon) in the pond with commercial. Main causes why we choose livestock tiger prawn because this business is very clear prospects, which demand for prawn very high in the local market also oversea and it having ability to give a high profit. Members of partnership are agreed to use Tok Bali Tiger Prawn for name of their company. This livestock have operation at Lot 195, Kampung Cherang Ruku, Daerah Semerak, Jajahan Pasir Puteh, and Kelantan. This location is very applicable for livestock tiger prawn and many facilities at there like nearly the road, river, electrical, water supply and telephone. These businesses expect will start on for starting that. We need RM 260 000 for capital contribution from members of partnership is RM 120 000 and balance is loan from Bank Pertanian Malaysia Berhad.